Triploidy in a Live-Born Extremely Low Birth Weight Twin: Clinical Aspects - Vakrilova, Liliya; Hitrova-Nikolova, Stanislava; Bradinova, Irena (Journal of Pediatric Genetics, 2020)
Triploidy is a rare chromosomal aberration characterized by a karyotype with 69 chromosomes. Triploid fetuses usually are miscarried in early pregnancy. We present a case of a triploid twin and a genetically unaffected co-twin, conceived through in vitro fertilization. A discordant growth was registered at 20 weeks of gestation. Cesarean section was performed at 355/7 gestational week. The second twin was extremely growth restricted female (780 g) with oligohydramnios and severe respiratory distress, and died at 20 hours of age. The autopsy revealed unilobar left lung, bilobar right lung, and cysts of the terminal bronchioles. Quantitative fluorescent polymerase chain reaction detected triploidy compatible pattern. So, early intrauterine growth restriction may be a sign of triploidy, which must be proven by pre or postnatal genetic testing.
Keywords: triploidy; intrauterine growth restriction; lung anomaly; twin pregnancy